"This is a holy place of Ama Jomo": buen vivir, indigenous voices and ecotourism development in a protected area of Bhutan. Issue 6 (3rd June 2017) - Karst, Heidi
ABSTRACT: Common definitions of ecotourism address the need to benefit the well-being of local people; in reality, ecotourism is often supported or dominated by external agents. Local ideological, social and cultural values may be overlooked, thereby disenfranchising local and indigenous stakeholders. This paper examines indigenous perceptions of ecotourism and well-being, and how they relate to ecotourism practices in three Brokpa communities of the first protected area in Bhutan to become a special tourism destination. A range of methods (e.g. semi-structured interviews, participatory mapping) was used and data analysis was couched in the context of buen vivir (living well), an indigenous concept of well-being. Findings indicate that: (1) perceptions of ecotourism vary between community members and contrast with the official park definition; (2) well-being is conceived in diverse ways but corresponds to key features of buen vivir ; (3) indigenous worldviews are pervasive, and shape social values and spiritual beliefs in connection to nature; and (4) indigenous cosmologies and traditional values may be strengthened through their integration into modern policies and institutions. This research contributes more non-Western voices to the literature, a concept and mode of analysis for well-being that embraces an indigenous ontology, and empirical insights on indigenous communities in protected areas.